PREPARATION OF FINANCIAL STATEMENTS BASED ON FINANCIAL ACCOUNTING STANDARDS FOR ENTITIES WITHOUT PUBLIC ACCOUNTABILITY (SAK ETAP) AT BUMDESMA IN SUMEDANG REGENCY - Erpi Rahman; Ima Sri Yuhartini; Risna Nurhayati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the implementation of Accounting Standards for Entities Without Public Accountability (SAK ETAP) and the rearrangement of financial statements based on SAK ETAP. This study focuses on the Joint Village-Owned Enterprises (BUMDESMA) of Sembada Darmaraja, located at Jalan Raya Darmaraja-Cibugel No. 29, Kaum Hamlet, Darmaraja Village, in the Darmaraja District. Data is gathered by observation, interviews, and documentation. The data analysis used is by collecting data, reduction data, presenting data, stages of preparing financial statements, analyzing conformity to SAK ETAP and compiling financial statements. The finding reveals that BUMDESMA Sembada Darmaraja presents only presents the Balance Sheet, Income Statement, and Operational Report of UPDB (Revolving Fund Management Unit). Meanwhile, SAK ETAP comprises of a Balance Sheet, Income Statement, Statement of Changes in Equity, Statement of Cash Flows, and Notes to Financial Statements to present financial statements. Thus, the financial statements are rearranged based on SAK ETAP.